Campaign GNSS results on rocky outcrops west of former Larsen B ice shelf, 2014-2015 - Hooper, Andrew; Palamartchouk, Kirill (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
During the 2014/2015 season six temporary GNSS stations were deployed on rocky outcrops west of the former Larsen B ice shelf by the University of Leeds and BAS, in the region of the Flask and Leppard Glaciers. This was carried out as part of the NERC funded UKANET project. This is an area we have targeted with a space-based technique called radar interferometry (InSAR), which can provide dense measurements of uplift rates, and the temporary GNSS network were deployed to better understand the contribution of atmospheric noise to the InSAR results. Four were taken out in the same season, while the other two were pulled in the 2015/2016 season. Funding was provided by NERC grant NE/L006065/1. : GPS and GLONASS Data were gathered using Leica GS10 receivers and Leica AS10 antennas connected to a car battery with a solar panel attached. The antennas were fixed on 30cm masts screwed onto a cemented pin. The sample rate was set to 15s. The instruments ran until power ran out due to lack of insolation during winter. The GPS data only were processed using the NASA JPL GPS- Inferred Positioning System (GIPSY) software. : Leica GS10 receivers and Leica AS10 antennas : High quality for the most part, but missing data towards end of the time series for UKA3 and UKA4, when batteries reached a low charge. Uncertainties are included in the data files.